Motion Survey Analysis of Freestyle Swimming Technique Skills in Young Athletes Aged 10-11 Years - Erick Burhaein; Aradia Rozak; Jewelson Medel Santos (JUMORA: Jurnal Moderasi Olahraga, 2023)
This research was conducted to determine the skills of freestyle swimming techniques of athletes 10-11 years nemo swallow swimming club in 2022. Participants in this study were Nemo Wallet Swimming Club KU IV athletes aged 10-11 years with 11 athletes. This research is a quantitative descriptive study. The method used is a survey of athletes who perform freestyle swimming by measuring the time taken by athletes in freestyle swimming at a distance of 25 meters. Based on the results of the study, it was obtained that as many as 8 athletes (73%) have excellent freestyle swimming ability, 1 athlete (9%) has good 25 m freestyle swimming ability, 1 athlete (9%) has sufficient freestyle swimming ability, 1 athlete (9%) has less freestyle swimming ability, and 0 athletes (0%) have very less freestyle swimming ability. Based on the results of the research concluded that freestyle swimming skills measured using stopwatches in athletes aged 10-11, from these data can provide an illustration that the category of 25 m freestyle swimming ability in Nemo Wallet Swimming Club athletes is a category (excellent), with a total of 8 athletes. Contributing to further research is conducting research on more intense exercises on freestyle swimming techniques as well as strategies for improving athletes' abilities in freestyle swimming. With this research, it is hoped that it can be used as a reference material for coaches regarding the level of athlete skills. With the discovery of several athletes who have the ability to swim freestyle under the good category, it is necessary to make efforts to improve the ability of athletes in order to achieve the good categoryKeywords: Surveys, Swimming Skills, Freestyle, athletes